Hypnotizing Maria : a story - Bach, Richard (Charlottesville, VA : Hampton Roads Pub., 2009)
"An exploration of deep spiritual and philosophical issues through the eyes of a pilot"--Provided by publisher.
Keywords: Air pilots -- Fiction